PENGARUH PUPUK KOMPOS DAN JARAK TANAM TERHADAP PERTUMBUHAN, KOMPONEN HASIL DAN HASIL KEDELAI (GLYCINE MAX (L) MERRILL) VARIETAS “ANJASMORO”. - Agustini, Agustini; Tadjudin, E; Purnomo, Dwi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This experiment aims to determine the effect of compost fertilizer on growth, yield components and yield of Soybean (Glycine Max (L) Merrill) Anjasmoro variety. This experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the study was carried out from August to November 2021. The location is located at an altitude of ±50 m above sea level (masl), the soil type is Latosol and Regosol association, including type D (moderate) rain. The experimental method used was the experimental method with a factorial randomized block design (RAK), the treatment consisted of two factors which were repeated three times. The first factor is compost, which consists of three levels, namely compost 5 tons/ha, 10 tons/ha, and 15 tons/ha. While the second factor is the spacing which consists of three levels, namely the spacing of 40 cm x 30 cm, 40 cm x 40 cm and 40 cm x 50 cm. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-Knott cluster further test analysis. To determine the correlation between the treatment with the components of growth and yield of soybeans, the correlation used is the Product Moment correlation coefficient.The results showed that: (1) There was a significant effect between the combined dose of compost and plant spacing, (2) Combination of compost at a dose of 10 tons/ha gave the highest dry seed weight per plot at a spacing of 40 cm x 50 cm on Anjasmoro soybean. namely 929, 13 grams/plot or equivalent to 1.55 tons/ha, and (3) There was a significant correlation between plant height at 21 DAP and 28 DAP, and root volume at 21 DAP and 28 DAP and dry seed weight per plot.